Metaphilosophical themes : naturalism, rationalism and the conceptions of philosophy - Pettersson, Henri (fi=Turun yliopisto|en=University of Turku|, 2019)
This study belongs firmly to the genre of metaphilosophy, as it reflects on topics pertaining to the subject matter, method and aim of philosophy itself by using philosophy’s own usual tools and approaches. The contents of this study are divided into four main chapters, which have their own specific topics and goals. In the first chapter the various manifestations of philosophy’s multifaceted identity are under focus. We can clarify the diversity evident in philosophy by introducing the notion of conception of philosophy. These are sets of philosophical theses, which present us with their disinctive takes on philosophy’s topics, methods and purposes. Conceptions of philosophy must, however, be strictly separated from other related phenomena (such as schools, traditions and movements), which are in their own ways involved in creating the pluralism existing in philosophy. To close the chapter I argue for the importance of these themes. The second chapter examines the distinctive point of view and aim of metaphilosophical reflection and chronicles its past. I also defend the value of this inquiry. Although metaphilosophising as a form of philosophical research has a long past, it has only recently emerged as its own distinct branch in philosophy. Thus philosophers still use this name in numerous different ways, and there has not previously been many in-depth overviews of the nature of metaphilosophical reflection itself. To remedy this situation, I clarify the nature of metaphilosophy as a ”philosophy of philosophy” of sorts, which is best viewed as an internal enterprise operating within the bounds of philosophy proper. I also examine the potential problematics inherent in this arrangement. The third chapter presents as a metaphilosophical case study the so-called naturalism-question. This issue pertains to the way how to properly construe the role, province and stature of philosophy in relation to the undertakings of empirical special sciences. However, in the discussions between naturalists and anti-naturalists (who are in this work represented by advocates of the view known as metaphilosophical rationalism), there exists misunderstandings and toxic forms of rhetoric. I point out these aspects in hopes of making them more apparent. At the chapter’ end I also consider the significance of the naturalismquestion for the near future of philosophy. The fourth chapter studies the methodology of the so-called armchair philosophy, that is, intuitions and the thought experiments which are used to elicit and articualte such intuitions. Despite the attention these methods have received in the recent metaphilosophical literature, there still exists confusions and disagreements in this topic. I hope to set at least few of these issues straight with my metaphilosophical examination of these themes.

Tutkimus kuuluu yleisesti metafilosofian lajityyppiin, sillä siinä tarkastellaan filosofoinnin kohteisiin, menetelmiin ja tavoitteisiin liittyviä aiheita käyttäen tässä apuna filosofian omia näkökulmia. Työn tarkempi sisältö jakautuu neljään päälukuun, joilla on omat tavoitteensa. Niinpä tutkielman kysymyksenasettelut voidaan esittää parhaiten tätä rakennetta peilaten. Ensimmäisessä pääluvussa tutkitaan filosofian moniäänisen identiteetin erilaisia ilmenemismuotoja. Filosofiassa esiintyvää rikkonaisuutta voidaan selventää filosofiakäsitysten ajatuksen avulla, millä tarkoitetaan sellaisia filosofoinnin aiheisiin, menetelmiin ja tavoitteisiin eri tavoin kantaa ottavia kokonaiskuvia, jotka näin tehdessään ehdottavat omat filosofisesti rakentuneet vastauksensa siihen, mistä filosofiassa lopulta oikein on kyse. Filosofiakäsitykset tulee kuitenkin erottaa muista filosofian hajanaiseen profiiliin vaikuttavista ilmiöistä, kuten koulukunnista ja virtauksista. Pääluvun päätteeksi puolustetaan filosofiakäsitysten välisten keskustelujen tärkeyttä. Toinen pääluku esittelee metafilosofisen pohdinnan näkökulmaa, tavoitteita ja historiaa sekä puolustaa sen tarpeellisuutta. Vaikka metafilosofialla on ilmiönä pitkä historia filosofiassa, on se vasta hiljattain eriytynyt omaksi filosofian osa-alueekseen. Niinpä filosofit käyttävät tätä nimeä eri tavoin, eikä metafilosofisen reflektion lähtökohdista ole aiemmin tarjottu montaa systemaattista kokonaisesitystä. Selvennän metafilosofisen pohdinnan luonnetta eräänlaisena filosofian sisäisenä ”filosofian filosofiana” ja tarkastelen siihen liittyviä potentiaalisia ongelmallisuuksia. Kolmas pääluku esittelee metafilosofisena tapaustutkimuksena niin kutsutun naturalismi-kysymyksen, joka koskee sitä, miten filosofian työnkuva, reviiri ja arvovalta ymmärretään suhteessa kokemusperäisiin luonnontieteisiin. Naturaistien ja antinaturalisteja tässä työssä edustavien rationalistien kyseisestä aiheesta käymissä metafilosofisissa keskusteluissa esiintyy kuitenkin paljon väärinkäsityksiä ja ennakkoluuloja, joita pyrin omalla tarkastelullani oikomaan. Pääluvun kuluessa arvioidaan myös naturalismi-kysymyksen painoarvoa filosofian lähitulevaisuuden kannalta. Neljäs pääluku tarkastelee niin kutsutun nojatuolifilosofian tutkimusmenetelmiä, joista naturalistit ja rationalistit ovat eri linjoilla. Näitä tutkimusmenetelmiä ovat intuitiot sekä niitä elähdyttävät ja artikuloivat ajatuskokeet. Näiden ilmiöiden osakseen saamasta huomiosta huolimatta aihepiirissä esiintyy edelleen paljon erimielisyyttä ja sekaannuksia koskien niiden luonnetta ja alkuperää, mitä tilannetta korjaan omilla tarkennuksillani.